Clinical Efficacy of Probiotic Supplementation in Reducing the Severity of Irritable Bowel Syndrome (IBS) Symptoms in Athletes - A Literature Review - Michalski, Łukasz; Mszyca, Igor; Browarska, Emilia; Miemczyk, Katarzyna; Wołek, Filip; Gajewska, Nicole; Mularczyk, Karolina; Kucharski, Kacper; Aksamit, Anna; Superson, Katarzyna (Quality in Sport, 2026)
Introduction: Intense physical exertion in athletes amplifies dysregulation of the gut-brain-microbiome axis, causing visceral ischemia and intestinal barrier dysfunction, which intensifies the symptoms of irritable bowel syndrome (IBS). Objective: To evaluate the clinical efficacy of probiotic therapy in reducing IBS symptoms in physically active individuals and to analyze the mechanisms of action in the context of training loads. Methodology: The literature review was based on a structured search of medical and sports databases. Keywords included: “irritable bowel syndrome,”, “athletes,” “probiotics,” “intestinal barrier,” “gut-brain axis,” and “physical exertion.” Priority was given to current clinical studies, including randomized controlled trials, multicenter meta-analyses, network meta-analyses, and official positions of international sports medicine societies. Articles were analyzed for pathophysiological mechanisms under training loads, the clinical efficacy of specific bacterial strains, safety, treatment duration, and doping-free status Results: Supplementation with targeted strains effectively seals epithelial tight junctions, reduces exercise-induced endotoxemia, and stimulates the production of short-chain fatty acids. Probiotics significantly reduce abdominal pain and bloating, especially in the diarrhea-predominant subtype, reducing the irritable bowel syndrome symptom severity score. Their potential to alleviate exercise-induced muscle damage and accelerate recovery has been demonstrated. Reducing visceral symptoms improves quality of life and the psychophysical profile of athletes, lowering pre-competition anxiety and peripheral fatigue. Conclusions: Targeted probiotic therapy is a safe, non-pharmacological strategy that, by eliminating gastrointestinal barriers, indirectly supports athletes’ exercise capacity.It is recommended to implement supplementation during the preparatory period using products certified for anti-doping purity.